2022
DOI: 10.18632/aging.204400
|View full text |Cite
|
Sign up to set email alerts
|

Restraint stress of female mice during oocyte development facilitates oocyte postovulatory aging

Abstract: Studies suggest that psychological stress on women can impair their reproduction and that postovulatory oocyte aging (POA) might increase the risk of early pregnancy loss and affect offspring's reproductive fitness and longevity. However, whether psychological stress during oocyte development would facilitate POA is unknown but worth exploring to understand the mechanisms by which psychological stress and POA damage oocytes. This study observed effects of female restraint stress during oocyte development (FRSO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 46 publications
(52 reference statements)
0
0
0
Order By: Relevance
“…In animal experiments, chronic stress has been shown to disrupt the estrous cycle, alter hormone levels, and decrease follicle numbers in mice [10,11]. Stress can also induce cytoplasmic fragmentation, apoptosis, spindle disorders, and oxidative stress, accelerating the aging of mouse oocytes and increasing the risk of early pregnancy failure [12].…”
Section: Introductionmentioning
confidence: 99%
“…In animal experiments, chronic stress has been shown to disrupt the estrous cycle, alter hormone levels, and decrease follicle numbers in mice [10,11]. Stress can also induce cytoplasmic fragmentation, apoptosis, spindle disorders, and oxidative stress, accelerating the aging of mouse oocytes and increasing the risk of early pregnancy failure [12].…”
Section: Introductionmentioning
confidence: 99%
“…However, the mechanisms underlying increased STAS levels in aging oocytes are largely unclear. Kong et al [11] and Chen et al [12] have reported that cytoplasmic calcium is correlated with STAS in aging mouse oocytes. Cui et al [13] observed that cytoplasmic Ca 2+ levels were increased in rat oocytes undergoing spontaneous activation during postovulatory aging.…”
Section: Introductionmentioning
confidence: 99%